Model characteristics of sensory-motor reactions and perceptions of specific wrestlers of different styles of confrontation - Tropin Yura; Vyacheslav Romanenko; Viktor Ponomaryov (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to develop a model characteristics of sensory-motor reactions and perceptions of specific wrestlers of different styles of conducting fight. Material & Methods: theoretical analysis and generalization of scientific and methodological literature, modern competitive activity, generalization of best practices, psycho-physiological research methods, methods of mathematical statistics. The investigations, which were attended by 46 athletes engaged in different kinds of wrestling (freestyle, Greco-Roman wrestling, judo, sambo) with expertise from 1 to discharge the master of sports of international class, different ages (from 18 to 35 years). Results: based on the test results determined pedagogical level of psychomotor reactions and perceptions of specific wrestlers basic styles of conducting fight. Conclusions: it determined that the level of development of those or other psychomotor reactions and specific perceptions of athletes has a certain relationship with the typical style of the match.